Avaliação de métodos genotípicos e caracterização de heterorresistência em pacientes com tuberculose - Lida Jouca de Assis Figueredo (2018)
The difficulty in detecting resistance may lead to inadequate treatment and therapeutic failure and as consequence increase the spread of resistant bacteria, which can generate heteroresistance. The heteroresistance is the coexistence of drug-sensitive and sensitive strains in the same individual, considered the preliminary stage for total resistance. The objective of this study was to evaluate different genotypic methods for the detection of Mycobacterium tuberculosis heteroresistance to rifampicin and isoniazid drugs and their characterization. A total of 654 M. tuberculosis isolates of 654 patients in the state of Minas Gerais from 2009 to 2017 were included. The genotype MTBDRplus® and genomic sequencing were used to detect heteroresistance and Mycobacterial Interspersed Repeat-Unit-Variable-Number-Tandem Repeat (MIRU-VNTR) for characterization of mixed infection and clonal heterogeneity in heteroresistant isolates. Of the 654 isolates, 520 were sensitives and 134 resistant, of which 29 had heteroresistance to rifampicin and/or isoniazid. GenoType MTBDRplus® detected heteroresistance in 26/29 (89.7%) in rpoB, 5/29 (17.2%) in katG and 2/29 (6.9%) in inhA, three of which were concomitant in the rpoB and katG. In one isolate, the heteroresistence was present in the three genes. Sequencing detected heteroresistance in 7/29 (24.1%) in rpoB, 3/29 (10.3%) in katG and none in inhA. In one isolate, heteroresistance was concomitant in the rpoB and katG genes. MIRU-VNTR detected mixed infection in three heteroresistance isolates, presenting two distinct alleles at two or more loci suggesting the presence of two different strains, being 2/3 Ugandal/Haarlem and 1/3 LAM/Ugandal. The clonal heterogeneity occurred in four isolates that presented two distinct alleles in only one locus and proved to be of the LAM lineage. The socio-demographic profile of patients with heteroresistance was predominantly male 23/29 (79.3%), with the age range between 35-59 years old (69%) and race / black color 17/29 (58, 6%). Alcoholism was the major comorbidity 12/29 (41.4%). The cure occurred in 15/29 (51.8%), abandonment in 5/29 (17.3%), TB death in 3/29 (10.3%), 2/29 (6.9%) in treatment, 1/29 (3.4%) non-TB death and 3/29 (10.3%) had no known outcome. GenoType MTBDRplus® was the genotypic method that most detected heteroresistance. MIRU-VNTR demonstrated mixed infection and clonal heterogeneity. Of the patients who presented heteroresistance the majority had previous treatment and had a history of abandonment.